Integrated Multicriteria Decision Model for Software Project Selection at PT Hexavara Tech - Ridwan Taofiq Firdaus; Udisubakti Ciptomulyono (Jurnal Teknik ITS, 2021)
As a relatively young software company, PT. Hexavara Tech needs to select incoming projects since the number of requests exceeds the amount that the company can manage. Currently, there are no guidelines for selecting projects, so the project selection process is less structured and subjective. In fact, project selection is faced with several qualitative and quantitative criteria that tend to be conflictual in achieving objectives. So in this study, the integration of Analytical Hierarchy Process (AHP) and Goal Programming (GP) methods is used to select software projects that consider limitations and multi-objectivity. Based on the calculation of the level of importance of the criteria using AHP, the sequence of project selection criteria is obtained, namely profit for the company (0.287), potential development of the project scope (0.155), initial development capital (0.1), the opportunity to get relations from clients (0.097), conformity to team capabilities (0.093), risks contained (0.078), increasing the value of the company's portfolio (0.073), the opportunity to create a template for the next project (0.07), and the opportunity to learn new technology (0.047). After the optimization process using GP, the best final results are obtained, namely the e-wallet development project of savings and loan cooperatives, development of an android-based online motorcycle taxi application, development of e-commerce design works, development of overseas money transfer applications, and development of a website framework for cross border e-commerce